MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH MELALUI METODE PROJECT BASED LEARNING BERBASIS LESSON STUDY - Eva Nurul Malahayati (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2015)
The objective of this study is to see improvement to solve problem in the SBM course of the students of Biology Department at Malang State Univetsity using Problem Based-Learning and Lesson Study Basis. Ths study implements classrom action research with two cycles staging Plan, Do, and See as research strategies and assigned 24 students as subject. The study found the following findings: (1) Cycle 1: achievement to solve problems at the first and the second meeting are: 73.25% and 75.75% with the avarage 74.5%; (2) Cycle 2: respectively 71.67% at the first meeting, 80.5% second meeting, 82.33% third meeting and the avererage 78.2%. In summary, improvement on problem solving competency increases 3.7%.